(untitled) (MAUSAM, 1979)
The problem of stress accumulation near a locked vertical rectangular strike-slip fault is considered. The fault is taken to be situated in a visco-elastic half-space. It is assumed that tectonic forces maintain a steady shear stress far away from the fault. Exact solutions are obtained for the displacements and stresses in the system and it is shown that, in the absence of fault-slip, there would be a steady accumulation of shear stress near the fault., which would lead to a sudden slip on the fault, resulting in an earthquake, under suitable conditions, which are determined. The exact solutions also show that the accumulation of shear stress would again take place after the fault-slip. It is shown that, under suitable conditions, this would lead to another slip on the fault after a sufficient time. The analytical solutions can be used to compute the influence of different factors, such as, the dimension of the fault, the effective viscosity of the lithosphere and the stress system maintained by tectonic forces, on the time required for the shear stress accumulation to reach the level necessary to cause fault slip. It is also shown that, if adequate data are available on the ground deformation on the surface near the fault, it would be possible to obtain estimates of the probable times of fault slip. This may be of considerable use in earthquake prediction and in the estimation of changes in the seismic risk near the fault with time. Finally, it is shown that it would also be possible to obtain estimates of the effective viscosity of the lithosphere from a comparison of theoretically calculated results and suitable observational data, if available.